Green supply management and green marketing strategy on green purchase intention: SMEs cases - Dyah Sugandini; Muafi; Christin Susilowati; Yuni Siswanti; Wirman Syafri (Journal of Industrial Engineering and Management (JIEM), 2020)
Purpose: This study aims to analyze green supply chain management (GSCM) and green marketing strategies (GMS) to green purchasing intentions (GPI). This study conducts on craft SMEs in the Special Region of Yogyakarta, Indonesia. Design/methodology/approach: This study uses primary data which is obtained through questionnaires. The unit of analysis in this study is organizations and individuals. The sampling technique is purposing sampling, with the criteria of SMEs that conduct environmentally friendly production processes and consumers who have ever bought green products. Data analysis uses structural equation modeling. Research limitations/implications: This study is limited by relatively small sample size. The sample is only environmentally oriented SMEs. Large companies that are also environmentally friendly have not been included as samples in this study, so the results of this study only generalized to SMEs. Future research should accommodate these two types of companies, namely SMEs and companies, so that it can be easier to generalize the findings and allow different tests of GSCM to be applied to SMEs and large companies. This study only analyzed GSCM from two dimensions, namely GP and GCC. Other variables that can be used to explain GSCM are internal environmental, green information systems, eco-design and packaging. Practical implications: GSCM can be started with conducts the right GP and always coordinating with consumers which related to green products. GP (green purchasing) and GCC (green consumer cooperation) as GSCM elements have a strong association in predicting the success of a green marketing strategy. It is expected that SMEs should pay attention to the raw material purchase so that the problem of environmentally friendly raw materials can be truly obtained to enter the production process and produce environmentally friendly products. Originality/value: This study analyzes the relationship between GSCM practices and organizational performance in the green marketing and business strategies context, where there is still a scarcity of studies in this context. Besides that, there is an increase in awareness of green operations and green marketing in Asia, but the relevant studies in Asian countries have not been conducted much, especially in Southeast Asia. The result of this study proves that the GSCM model can increase value along the supply chain by emphasizing green supply chain management and green marketing.
Keywords: 650; Green supply chain; green marketing and green product